Pedagogical strategies and evaluations used with target audience students of Special Education according to the account of the ordinary and special education teachers (Práxis Educativa, 2017)
This paper analyses the account of common classroom teachers on the teaching strategies used with the possible target audience students of special education (TASSE) before forwarding them to the specialized educational service (SES) in multifunctional resource classrooms (MRCs), as well as analyses the evaluation criteria established with those who came to receive such service, and the account of special education teachers about the assessments used with the TASSE, after receiving the SES in MRCs. For data collection, two interview scripts were used, one of which was answered by 30 ordinary classroom teachers and the other by five special education teachers. The results suggested that the pedagogical strategies and assessments directed at the TASSE were decisive factors to identify whether the policy proposals related to inclusive education were being effectively implemented in elementary schools. Keywords: Pedagogical strategies. Assessment. Special Education.